TANGGUNG JAWAB HUKUM PIMPINAN REDAKSI LEMBAGA PENYIARAN TERHADAP PEMBERITAAN YANG MELANGGAR KODE ETIK JURNALISTIK - Rizky Randa Safaatulah (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT The mass media functions as a vehicle for mass communication, disseminating information, and forming opinions in society. The press is a social institution and vehicle for mass communication that carries out journalistic activities including searching, obtaining, possessing, storing, processing, and conveying information in the form of text, sound, pictures, sounds, and images, as well as data and graphics as well as other forms using media print, electronic media, and all types of channels available (Article 1 General Provisions of the Press Law)This type of research used in this study is a type of normative legal research, which is a legal research method that uses a statutory approachThe results showed that the press responsibility after the enactment of Law Number 40 of 1999 concerning the press, was explicitly regulated in the explanation of Article 12 and Article 18 paragraph (2), the sound of the article namely: Article 12 Press companies are required to announce the name, address, and person in charge openly through the media concerned; specifically for press releases plus names and printing addresses.Based on the explanation of Article 12 of Law Number 40 of 1999 concerning the Press, it is stated that the person in charge is the person in charge of the press company which includes the business field and the editorial field, as long as it involves criminal liability to adhere to the applicable laws and regulations. Article 18 paragraph (2) Press companies that violate the provisions of Article 5 paragraph (1) and paragraph (2), as well as Article 13 are convicted, with a maximum fine of Rp 500,000,000.00 (five hundred million rupiahs) Keywords: Publications, children, criminal offenders